Mixed Ligand Binuclear Complexes of Copper(II) and Cadmium(II) with Adenine and 1,4-Diazabicyclo[2.2.2]octane (Dhaka University Journal of Science, 2022)
Mixed ligand binuclear complexes of Cu(II) and Cd(II) with adenine (Ade) and 1,4-diazabicyclo[2.2.2]octane (DABCO) havebeen synthesized at a metal to ligands (M:L:L′) molar ratio of 1:1:1 in aqueous medium under ambient conditions. All synthesizedcomplexes are powdery solids of different colours, slightly soluble in hot water and decompose at high temperature. Characterizationof the complexes was accomplished using various analytical techniques, e.g. metal and chloride content analysis, Fourier transformspectrophotometer (FT-IR), UV-visible spectrophotometer, magnetic measurement, and thermal analyses. The metal and chloridecontents analyses of the complexes reveal to their stoichiometry [M2Cl2(Ade)2(H2O)2(DABCO)]Cl2 [M = Cu(II) or Cd(II)]. Analyticaldata suggests that they are homo metal symmetric binuclear complexes comprises of two [MCl(Ade)(H2O)] moieties in betweena DABCO molecule is N,N′-bridge bonded. The arrangements of the ligands around the metal centers are essentially tetrahedralinvolving N(9) of deprotonated imidazole moiety, one Cl- ion, one oxygen from the water molecule and one tertiary N atom fromDABCO completing the coordination. Proton migration occurs from N(9) to the N(1) site resulting into a zwitterionic form ofadenine, additionally N(3) site of which is hydrogen bonded with the coordinated water molecule. Electrochemical redox behaviourof Cu(II) in presence of adenine and DABCO in the aqueous medium was also studied. It exhibits quasi-reversible one-electrontransfer processes.Dhaka Univ. J. Sci. 70(1): 28-33, 2022 (January)